The emerging principle of free, prior and informed consent in development: evaluating development projects in the Limpopo Province of South Africa - Mukwevho, Naledzani Hendrick (My University, 2019)
The problem that I wish to address in this thesis is the failure by development agents, be it corporations or government departments, to obtain genuine consent from local communities before developmental projects can be launched in their territories or localities. The research aims to investigate if the application of the emerging principle of Free, Prior and Informed Consent (FPIC) could assist in obtaining genuine consent from affected communities; and to capacitate such communities to fully understand the implications of the proposed projects on their lives before they can agree or disagree to such projects taking place. Theoretical and practical research in the form of case studies was conducted to trace development patterns in South Africa and to establish if FPIC, or at least its spirit, has been applied in development projects. The results are that although South Africa has policies and a legislative framework that is in line with FPIC, the country has not formally adopted this principle. Neither has the principle been fully applied by development agents when they carry out their projects in communal lands. Consequent to these observations, I recommended that South Africa considers to formally adopt the FPIC principle as a policy, and if possible, legislate it; corporate organisations or institutes such as the Minerals Council of South Africa, for example, should adopt the FPIC principle and make its implementation by their members compulsory; and Government must ensure that every Act of Parliament that deals with development as well as land and environmental management incorporates public participation and consent pre-requisites for the granting of licences to carry out development project in lands belonging to local communities.
A thesis submitted in fulfilment of the requirement for the degree Doctor of Philosophy (PhD) to the Faculty of Commerce, Law and Management, School of Law, University of the Witwatersrand, Johannesburg, 2019
Keywords: Project management; Community development